Pengaruh Kemajuan Teknologi Terhadap Kehidupan Masyarakat Dalam Perspektif Sosial Budaya: Indonesia - Putri, Adela; Safitri, Desy; Sujarwo (The Indonesian Journal of Social Studies, 2024)
Along with the development of science, advances in technology can no longer be denied. Humans are competing to create the latest innovations to improve their quality of life. Technological progress occurs when a person uses tools and intelligence to solve every problem he faces. B.J. Habiebie (1983: 14). This technological advancement has a considerable influence on various aspects of human life, one of which is on the socio- cultural aspect of the human being himself. The influence obtained is of course not only in the form of positive things but also can be in the form of negative things that change the order of human life in society.The data collection method used in this study is the internet searching method.